SERTA KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN KATERING DI KECAMATAN ILIR BARAT I PALEMBANG - Hepiarti, - (Universitas muhammadiyah palembang, 2016)
The purpose of this research are to know the influence of work dicipline, motivation and job satisfaction on employees performance of company catering in the District Ilir Barat I Palembang. The problems of this study whether there is a work discipline, motivation and job satisfaction on employees performance of the catering company in the District Ilir Barat I Palembang?.The data used in this study are primary data 84 respondent answers. Models analysis used multiple linear regresion and by testing the validity and reliability of instruments. Test charactistics data that is test of normality and linearity test. Test model consist of multicolinearity test and heterokesdatisitas test.The test result of Multiple linear regresion showed work discipline, motivation and job satisfaction have a significant effect on employees performance is 0,000. Partially work discipline of 0,012. Motivation effect of 0,032 and job satisfaction effect on employees performance of 0,033.This study indicates conformity with the theory of work discipline, motivation an job satisfaction. There is also compability with previous studies. Increased work discipline, motivation and job satisfaction also increases performance.